Factors Associated with Malaria Parasitaemia, Malnutrition, and Anaemia among HIV-Exposed and Unexposed Ugandan Infants: A Cross-Sectional Survey - Osterbauer, Beth; Kapisi, James; Bigira, Victor; Mwangwa, Florence; Kinara, Stephen; Kamya, Moses R.; Dorsey, Grant (Malaria journal, 2012)
Malaria, malnutrition and anaemia are major causes of morbidity and mortality in African children. The interplay between these conditions is complex and limited data exist on factors associated with these conditions among infants born to HIV-uninfected and infected women. Two hundred HIV-exposed (HIV-uninfected infants born to HIV-infected mothers) and 400 HIV-unexposed infants were recruited from an area of high malaria transmission in rural Uganda. A cross-sectional survey was performed at enrolment to measure the prevalence of malaria parasitaemia, measures of malnutrition (z-scores <2 standard deviations below mean) and anaemia (haemoglobin <8 gm/dL). Multivariate logistic regression was used to measure associations between these conditions and risk factors of interest including household demographics, malaria prevention practices, breastfeeding practices, household structure and wealth index. The prevalence of malaria parasitaemia was 20%. Factors protective against parasitaemia included female gender (OR = 0.66, p = 0.047), mother’s age (OR = 0.81 per five-year increase, p = 0.01), reported bed net use (OR = 0.63, p = 0.03) and living in a well-constructed house (OR = 0.25, p = 0.01). Although HIV-unexposed infants had a higher risk of parasitaemia compared to HIV-exposed infants (24% vs 14%, p = 0.004), there was no significant association between HIV-exposure status and parasitaemia after controlling for the use of malaria preventative measures including bed net use and trimethoprim-sulphamethoxazole prophylaxis. The prevalence of stunting, underweight, and wasting were 10%, 7%, and 3%, respectively. HIV-exposed infants had a higher odds of stunting (OR = 2.23, p = 0.005), underweight (OR = 1.73, p = 0.09) and wasting (OR = 3.29, p = 0.02). The prevalence of anaemia was 12%. Risk factors for anaemia included older infant age (OR = 2.05 per one month increase, p = 0.003) and having malaria parasitaemia (OR = 5.74, p < 0.001). Compared to HIV-unexposed infants, HIV-exposed infants had a higher use of malaria preventative measures and lower odds of malaria parasitaemia. Having a better constructed house was also protective against malaria parasitaemia. HIV-exposure was the primary risk factor for measures of malnutrition. The primary risk factor for anaemia was malaria parasitaemia. These findings suggest the need to better target existing interventions for malaria, malnutrition and anaemia as well as the need to explore further the mechanisms behind the observed associations.
Keywords: Malaria, Primary Risk Factor, Malaria Parasitaemia, Thick Blood Smear, Malaria Indicator Survey